A COMPARATIVE ANALYSIS OF KEYNESIAN AND MONETARIST THEORIES IN RESPONDING TO MODERN ECONOMIC CRISES - Linatul Uyun (Count : Journal of Accounting, Business and Management, 2025)
This study aims to conduct a comparative analysis of Keynesian and Monetarist theories in responding to modern economic crises, with particular attention to the COVID-19 pandemic and other recent macroeconomic disruptions. Using a qualitative library research method, the study synthesizes scholarly literature, policy reports, and institutional data from sources such as the IMF, World Bank, and academic journals published in the last decade. The results show that Keynesian fiscal interventions were more effective in achieving short-term recovery by boosting aggregate demand and reducing unemployment, especially in countries with strong institutional frameworks and fiscal space. Meanwhile, Monetarist approaches, focusing on price stability and money supply control, demonstrated greater strength in long-term inflation management, albeit with slower recovery rates. A key novelty of this research lies in its integration of both theories within a single adaptive policy framework, accounting for regional, institutional, and structural differences. Unlike many previous studies that treat these frameworks in isolation, this research reveals the potential effectiveness of hybrid fiscal-monetary strategies and underscores the need for theory-to-practice alignment in contemporary policy-making. The findings suggest that macroeconomic responsiveness requires not only theoretical rigor but also flexibility and context-sensitive application. In conclusion, this study contributes to modern macroeconomic thought by proposing a more inclusive and practical model of crisis response that reflects the evolving nature of global economic shocks and institutional realities.